The Impacts of Perceptions of Justice and Organizational Support on Employee Performance: The Moderating Role of Satisfaction with Management, in the Portuguese Context - Coelho, Arnaldo (2018)
The objective of this paper is to identify the impact of perceived organizational justice (POJ) and perceived organizational support (POS) on the individual performance (IP) of employees and on burnout (BUR), considering the moderating role of satisfaction with organizational management (SOM). The study uses a structured questionnaire to gather self-reporting data from a cross-sectional sample of 407 employees. Structural equation modeling (SEM) is used to test the proposed hypotheses, and a multi-group analysis is conducted to find how the perception SOM can impact on the suggested relationships. The results show that POJ and POS have a positive impact on psychological contract (PC) and affective commitment (AC). Happiness (HAP) and AC have a positive impact on IP and PC has a negative impact on the BUR. It was also possible to conclude that SOM moderates the relationships between PC and BUR and, between leader-member exchange (LMX) and AC. This investigation provides a better understanding and integration of these concepts and relationship of moderation in a single study and provides a model that depicts a chain of important effects that may inform strategies to secure positive human resources management outcomes.